Case Study: Efektifitas Head Control Exercise, Neck Capital Flexion, dan Standing Frame with Neck Collar Terhadap Kemampuan Head Control pada Cerebral Palsy Spastik Quadriplegi Athetoid - Hikmatul Azizah; Agus Widodo (LPPM STIKES Siti Hajar dan Insight Power, 2022)
The clinical picture of children with Cerebral Palsy (CP) premature birth often differs from normal births, namely the problem of low muscle tone wether in the eyes, face, neck, and body. In the case of a preterm child with CP, the child showed weak muscle activation with a collapsed neck. Delay in head control ability is a disorder that is often found in CP children due to problems in the central nervous system (CNS) which serves as the basis for movement that must be achieved for further movement development. Management of physiotherapy in this case aims to determine the effect of giving physiotherapy interventions in the form of Head control exercise, Neck capital flexion, and Standing frame with neck support (collar) to improve head control ability in CP children with a history of premature birth. The results of the study after having physiotherapy 6 times showed an increase in the GMFM (Gross Motor Function Measure) score from an average score of 14.2% to 15.6% and an increase in the duration of the head control ability in the prone position from 0 seconds to 10 seconds with the help of physiotherapist and in a sitting position from 8 seconds to 45 seconds independently. The conclusion of physiotherapy management in the form of Head control exercise, Capital neck flexion, and Standing frame with neck support (collar) can increase the gross motor score on GMFM and increase the duration of head control ability. Keywords: Cerebral Palsy, Head Control Neck Capital Flexion, Standing Frame, Gross Motor Function Measure